RETRACTED: Effects of Inbound Tourism on the Ecological Footprint. An Application of an Innovative Dynamic Panel Threshold Model - Li, Xiaojuan; Meo, Muhammad Saeed; Aziz, Noshaba; Arain, Hira; Ferraz, Diogo (Frontiers in Environmental Science, 2022)
Tourism has a significant negative impact on the environment. As a result, the local ecosystem is being depleted, resulting in pollution and waste problems. Hence, environmental challenges have grabbed the interest of policymakers and academics all across the world. This study uses a new and innovative dynamic panel threshold model to examine the relationship between inbound tourism and ecological footprint. This method was applied to the ten most visited destinations spanning 1995 to 2021. These findings demonstrate that inbound tourism and ecological footprint have a threshold effect. To be specific, we find that only a certain threshold of tourism is beneficial to the environment; beyond that point, increasing tourism is likely to cause ecological footprint. Additionally, economic growth, infrastructure investment, and energy all benefited the ecological footprint. But water availability negatively affects ecological footprint. The findings of this study may have important policy implications for policymakers.